Keeping Corruption at ‘Arms’ Length: The scope of the Foreign Corruption Practice Act in Combatting Corruption in the Arms Trade Industry - Adhikari, Nilaza (Kent Law Review, 2019)
In an era dominated by global conflict, terrorism and the increasing need for defence, it is unsurprising that global arms trade is thriving. According to the Stockholm International Peace Research Institute, arms trade accounts for roughly 40% of all corruption in global transactions. However,there is little literature regarding the extent to which existing anti-corruption regimes can or have combatted arms trade corruption. This essay aims to contribute to the discourse on arms trade corruption by critically evaluating the scope of the Foreign Corruption Practice Act (FCPA) in combatting corruption, in particular bribery,within the arms industry. The discussion commences with an introduction of the FCPA’s origins, functions and extraterritorial jurisdiction. This will be followed by an examination of corruption within the arms trade industry and the role defence offset plays in contributing to bribery. Attention will be paid to the FCPA’s method (or lack thereof) of tackling defence-offset corruption. Subsequently, the paper will draw on FCPA’s enforcement power and its fines system to explore its effectiveness. This section will also analyse the FCPA’s implementation within the United States (US) and whether the act has succeeded in its primary aim to safeguard US business against corruption, particularly in the arms industry. Through a discussion on the FCPA’s vagueness and exclusion of grease payments, the final section will critically evaluate the FCPA’s limitations in combatting arms bribery and corruption. Whilst the essay acknowledges the FCAP’s role in helping combat arms corruption, it emphasises on the FCPA’s limitation and calls for FCPA reform to combat arms corruption.